(untitled) (Journal of Bio-Science, 2024)
Azithromycin possesses low aqueous solubility leading to inadequate absorption and poor bioavailability after oral administration. Solid dispersion of azithromycin represented a formulation with enhanced dissolution and antibacterial activity. The study designed to evaluate the in-vivo potential of azithromycin-loaded solid dispersion in Escherichia coli-induced diarrheagenic (DEC) mice. Diarrhea was induced in Swiss Albino mice by the oral administration of bacterial culture (100 μl of 1010 CFU/ml) in high glucose Dulbecco’s modified Eagle’s medium (DMEM). The E. coli-infected diarrheal mice received oral administration of azithromycin-loaded solid dispersion, equivalent doses of pure azithromycin and/or vehicle (DMEM in high glucose) for 3 days; and their effects on diarrheal score, inflammatory markers, and histology of intestinal tissues were observed. Azithromycin-loaded solid dispersion treatment prevented diarrhea and retardation of growth in infected mice more efficiently than the equivalent doses of pure azithromycin. The E. coli-infected mice demonstrated soft feces with irregular intervals; however, the nature and frequency of feces were improved with azithromycin-loaded solid dispersion. The increased level of total white blood cells and % of neutrophil was also significantly decreased with solid dispersion of azithromycin. In contrast, pure azithromycin did not alter the counts compared to disease control mice. Furthermore, the colonic tissues of E. coli-infected mice showed loss of epithelial integrity with sub-mucosal edema and also associated with increased serum amylase and C-reactive protein levels. However, solid dispersion of azithromycin-treated mice exhibited restoration of colonic tissue structure with a significant attenuation in serum amylase and C-reactive protein levels compared to pure azithromycin and/or vehicle-treated mice. Solid dispersion of azithromycin was more effective against E. coli-infected diarrheagenic mice than the equivalent doses of pure azithromycin; and the effect was dose-dependent. J. Bio-Sci. 32(1): 69-82, 2024